Upregulation of Phosphatidylinositol 3-Kinase (PI3K) enhances ethylene biosynthesis and accelerates flower senescence in transgenic nicotiana tabacum L. - Dek, Mohd Sabri Pak; Padmanabhan, Priya; Sherif, Sherif; Subramanian, Jayasankar; Paliyath, Gopinadhan (MDPI, 2017)
Phosphatidylinositol 3-kinase (PI3K) is a key enzyme that phosphorylates phosphatidylinositol at 3'-hydroxyl position of the inositol head group initiating the generation of several phosphorylated phosphatidylinositols, collectively referred to as phosphoinositides. The function of PI3K in plant senescence and ethylene signal transduction process was studied by expression of Solanum lycopersicum PI3K in transgenic Nicotiana tabacum, and delineating its effect on flower senescence. Detached flowers of transgenic tobacco plants with overexpressed Sl-PI3K (OX) displayed accelerated senescence and reduced longevity, when compared to the flowers of wild type plants. Flowers from PI3K-overexpressing plants showed enhanced ethylene production and upregulated expression of 1-aminocyclopropane-1-carboxylic acid oxidase 1 (ACO1). Real time polymerase chain reaction (PCR) analysis showed that PI3K was expressed at a higher level in OX flowers than in the control. Seedlings of OX-lines also demonstrated a triple response phenotype with characteristic exaggerated apical hook, shorter hypocotyls and increased sensitivity to 1-aminocyclopropane-1-carboxylate than the control wild type seedlings. In floral tissue from OX-lines, Solanum lycopersicum phosphatidylinositol 3-kinase green fluorescent protein (PI3K-GFP) chimera protein was localized primarily in stomata, potentially in cytoplasm and membrane adjacent to stomatal pores in the guard cells. Immunoblot analysis of PI3K expression in OX lines demonstrated increased protein level compared to the control. Results of the present study suggest that PI3K plays a crucial role in senescence by enhancing ethylene biosynthesis and signaling.